Safety assessment in development and operation of modular continuous-flow processes. Issue 3 (24th April 2017) - Kockmann, Norbert; Thenée, Philipp; Fleischer-Trebes, Christoph; Laudadio, Gabriele; Noël, Timothy
Abstract : Improved safety is one of the main drivers for microreactor application in chemical process development and small-scale production. Abstract : Improved safety is one of the main drivers for microreactor application in chemical process development and small-scale production. Typical examples of hazardous chemistry are presented indicating potential risks also in miniaturized equipment. Energy balance and kinetic parameters describe the heat production potential and, together with heat transfer capability, the temperature development in a continuous flow reactor. Besides these calculation procedures, checklists for laboratory safety and risk assessment are the basis for improved laboratory work as well as for equipment-related safety discussions. For complete and larger chemical plants, hazard and operation (HAZOP) studies are the appropriate method of handling hazardous processes and their scale-up.